Distributed Autonomous Robotic Systems The 14th International Symposium - Correll, Nikolaus; Schwager, Mac.; Otte, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume of the SPAR series brings the proceedings of the fourteen edition of the DARS symposium on Distributed Autonomous Robotic Systems, whose proceedings have been published within SPAR since the past edition. This symposium took place in Boulder, CO from October 15th to 17th, 2018. The volume edited by Nikolaus Correll and Mac Schwager contains 36 scientific contributions cutting across planning, control, design, perception, networking, and optimization, all united through the common thread of distributed robotic systems.
From the content: Distributed Tunneling Reconguration of Sliding Cubic Modular Robots in Severe Space Requirements -- Consensus Control of Distributed Robots Using Direction of Arrival of Wireless Signals -- Distributed Reinforcement Learning for Multi- Robot Decentralized Collective Construction -- The Computational Complexity of Controller-Environment Co-design using Library Selection for Distributed Construction -- Molding a Shape-Memory Polymer with Programmable Matter.
Keywords: Control engineering; Robotics; Automation; Computational intelligence; Artificial intelligence; Control, Robotics, Automation; Computational Intelligence; Artificial Intelligence